ANALISIS DAMPAK PROGRAM PASAMAN SEJAHTERA DALAM MENINGKATKAN KESEJAHTERAAN MUSTAHIK PERSPEKTIF EKONOMI ISLAM (Studi Kasus Pada Baznas Kabupaten Pasaman, Provinsi Sumatera Barat) - Syahrul Gunawan; Zuwardi (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to determine the Impact of the Pasaman Sejahtera Program in Improving the Welfare of Mustahik from an Islamic Economic Perspective. The Pasaman Sejahtera program is a program for distributing zakat funds from BAZNAS Pasaman Regency in an effort to realize economic growth and the needs of the community, in the form of providing business capital assistance to underprivileged families or the poor and needy. The type of research used in this study is field research with a qualitative descriptive approach. The informants in this study were BAZNAS and mustahik who received zakat funds from the Pasaman Sejahtera program. The data obtained in this study came from observations and interviews which were then analyzed using data reduction techniques, data presentation and drawing conclusions. The results of this study indicate that the Pasaman Sejahtera program is able to provide better social and economic conditions in the lives of mustahik, although the economic impact created is not too significant. The economic impact is increasing the capacity of mustahik businesses, increasing income, fulfilling basic needs, reducing poverty rates and stimulating local economic growth. The impact on the social conditions of mustahik is the creation of solidarity and social networks among mustahik. In distributing the Pasaman Sejahtera program assistance, BAZNAS has implemented distribution principles in accordance with Islamic economic principles, namely the principle of justice and equality, the principle of brotherhood and compassion, and the principle of social solidarity. In Islam, welfare includes five things, namely in terms of religion, soul, mind, descendants and property. The welfare felt by the mustahik is first, in terms of religion, namely strengthening spiritual relationships with Allah SWT and also fellow human beings. Second, in terms of soul, namely giving the mustahik a sense of self-confidence and hope for a better life, thereby reducing the stress and anxiety that the mustahik has felt so far. Third, in terms of descendants, namely making the mustahik somewhat able to finance their children's school and build a better future for their descendants. Fourth, in terms of property, namely helping the mustahik develop their business.